Olive pomace lignin as a sustainable bio-based modifier for asphalt: performance, economic, and environmental evaluation - Ala Alobeidyeen; Amal Al-Hanaktah; Amani Abdallah Assolie (Discover Applied Sciences)
Abstract The pressing challenges of environmental pollution and the depletion of fossil resources have intensified the search for renewable and sustainable materials in the pavement industry. In response, this study investigates the potential of olive pomace lignin (OPL), a bio-product derived from agricultural waste, as a sustainable and eco-friendly modifier for asphalt binders and concrete mixtures. Unlike prior studies utilizing raw olive pomace or its ash, this research isolates lignin—a high-performance biopolymer—enhancing compatibility, stability, and mechanical performance. The OPL was extracted using acid hydrolysis and blended with asphalt binder at dosages ranging from 4 to 12%. Comprehensive laboratory evaluations, including penetration, ductility, softening point, rotational viscosity, Marshall stability, and resilient modulus tests, were conducted to assess the mechanical and rheological characteristics of asphalt binder and mixture performance. Results highlight that 10% OPL represents the optimal dosage, delivering improved stiffness, resistance to deformation, and thermal stability without compromising workability. Economic and environmental assessments demonstrate 22.3% cost savings, 5–7% energy reductions, and 6.1–9.8% lower CO2 emissions compared to conventional asphalt. These findings emphasize OPL’s role as a sustainable, high-performance alternative for modern infrastructure, promoting circular economy principles by transforming agricultural waste into functional materials for road construction.